Equity: concepts, meanings and implications for the Brazilian National Health System - Barros, Fernando Passos Cupertino de; Sousa, Maria Fátima de (Saúde e Sociedade, 2016)
This paper aims to review the different conceptual elements of equity that have been consolidated over time and the reading of its signification that is made in Brazil today, conceived as a way to achieve the guarantee and full advantage of rights to health, bearing in mind the concern to understand the differences, needs and particularities of different social groups. We emphasize the need to conceive equity in health as a process in permanent trans formation, which keeps changing its scope and comprehensiveness as results are achieved and new challenges occur. We propose to advance in the dis cussion of the topic to establish solid checkpoints that result in promotion of the equity needed to achieve the right to health, allowing the production of an objective improvement of health indicators, as well as of the citizen perception of his satisfaction concerning his/her health condition and of his/her family and community. Therefore, the ideal of a health system capable of providing what is neces sary for everybody, taking into account specificities and particular needs, can be achieved.